Pengaruh Model Problem Based Learning Berbantuan Media Wordwall terhadap Hasil Belajar Luas dan Keliling Persegi Peserta Didik Kelas IV di SD Negeri 15 Ulu Gadut - Putri, Elsa Nurdiana; Helsa, Yullys (Darul Yasin Al Sys, 2025)
This study aims to determine the effect of the Problem Based Learning model assisted by Wordwall media on the learning outcomes of the area and perimeter of squares of grade IV students at SD Negeri 15 Ulu Gadut. This type of research is quantitative research with a pre-experimental design in the form of one group pretest-posttest design. The research sample was grade IV A students selectecd using the Cluster Sampling technique, where the population consisted of all grade IV students at SD Negeri 15 Ulu Gadut consisting of 4 classes. The research instrument was in the form of multiple choice test questions for the pretest and posttest. The results showed an increase in student learning outcomes after the implementation of the Problem Based Learning model assisted by Wordwall media. This increase was evidenced by the average pretest score on the area and perimeter of square material of 30.654 and the average posttest score with the same questions was 67.842. Through data analysis using the Paired Sample t-Test which showed a significance value of 0.002 <0.05, which means that H0 is rejected and Ha is accepted. It can be concluded that there is a significant influence of the Problem Based Learning model assisted by Wordwall media on the learning outcomes of the area and perimeter of squares of grade IV students at SD Negeri 15 Ulu Gadut.